Arsenic(III) Immobilization on Rice Husk - Chaudhuri, Malay; Mohammed, Mohammed Ali (Journal of Science and Technology, 2012)
A number of large aquifers in various parts of the world have been identified with contamination by arsenic. Long-term exposure to arsenic in drinking water causes cancer of the skin, lungs, urinary bladder and kidney, as well as skin pigmentation and hyperkeratosis. Arsenic occurs in groundwater in two valence states, as trivalent arsenite [As(III)] and pentavalent arsenate [As(V)]. As(III) is more toxic and more difficult to remove from water by adsorption on activated alumina. In this study, immobilization (adsorption) of As(III) by quaternized rice husk was examined. Batch adsorption test showed that extent of adsorption was dependent on pH, As (III) concentration, contact time and rice husk dose. Maximum adsorption occurred at pH 7-8, and equilibrium adsorption was attained in 2 h. Equilibrium adsorption data were described by the Langmuir and Freundlich isotherm models. According to the Langmuir isotherm, adsorption capacity of quaternized rice husk is 0.775 mg As(III)/g, which is 4.3x higher than that (0.180 mg As(III)/g) of activated alumina. Quaternized rice husk is a potentially useful adsorbent for removing arsenic from groundwater.